Direction, legitimacy and structuration in technological innovation systems upscaling-insights from roadmaps for deepwater offshore wind energy - Bento, Nuno (2016)
This research investigates strategies aiming to accelerate the up-scaling of low- carbon innovations. We adopt the technological innovation systems (TIS) perspective to focus on structuration or system building processes, including key innovative activities. We analyze national roadmaps that have been developed for offshore wind energy in deep waters - more than 50 meters deep where most of the potential is expected but whose technologyis more immature . in Europe. The roadmaps analysis not only reveals how actors expect the TIS grow but also enables the understanding about the critical functions at this stage, such as direction of search and legitimacy.